38 Gait kinematics and kinetics in patients with and without chronic ankle instability: a statistical parametric mapping analysis. (12th October 2015) - Herb, CC; Patacky, T; Hart, J; Saliba, S; Blemker, S; Hertel, J
Abstract : Background: Chronic ankle instability (CAI) is associated with changes in gait biomechanics, which may be related to chronic dysfunction. Multivariate analysis of the lower extremity during gait may reveal unique biomechanical differences associated with CAI. Objective: To compare 3D kinematics and joint moments of the ankle, knee and hip and ground reaction forces (GRF) during gait. Design: Case-control study. Setting: Biomechanics laboratory. Participants: Forty young, active adults participated in this study (CAI: n = 20, control: n = 20). Interventions: Data was collected using a 3D motion analysis system while patients walked and jogged. Main outcome measurements: Statistical parametric mapping (SPM) was used to assess 3D GRF, joint angles and internal joint moments of the lower extremity of CAI and control participants. Results: During walking, the largest group difference was found in ankle frontal plane motion from 68–100% of the gait cycle with the CAI group having significantly more inversion (p < 0.001, mean difference = 3.2°, effect size = 0.95). During jogging, the greatest difference was found in sub-talar frontal plane kinematics from 20–92% with the CAI group having greater inversion (p < 0.001, mean difference = 4.6°, effect size = 0.81). Greater plantar flexion moments were found from 65–71% (p = 0.05, mean difference = 347.4 Nm/kg, effect size = 0.83) and greater eversion moments were found from 95–100% (p = 0.03, mean difference = 74.6 Nm/kg, effect size = 0.58) in the CAI group. Conclusion: SPM identified significant differences between CAI and healthy groups in frontal plane ankle motion and frontal and sagittal plane joint moments during gait. Greater inversion throughout the gait cycle may present a potentially injurious position. A faulty position of the rear-foot may require greater muscle function in order to correct the position of the joint resulting in greater eversion moments at the ankle. However, this kinetic change does not appear to correct the altered ankle position.